DON entry into the nucleus induces DNA damage, apoptosis and cycle arrest in GES-1 cells. (January 2023) - Hou, Silu; Cheng, Yuqiang; Wang, Zhaofei; Xia, Luming; Wang, Jian; Wang, Hengan; Sun, Jianhe; Ma, Jingjiao; Yan, Yaxian
Abstract: Deoxynivalenol (DON) is a mycotoxin produced by the genus Fusarium and belongs to the trichothecenes group B compound. At present, the mechanism of DON toxicity to mammalian cells is not fully understood. Since the stomach is the first physiological barrier against food contaminants, it is also the first target of exposure to toxins. In this research, we investigated the toxic effects of DON on human gastric mucosal epithelial cells (GES-1) as a model. We found that DON significantly inhibited cell activity, but did not induce ROS production in GES-1 cells. Although DON was unable to induce ROS production, the intracellular "redox homeostasis" was altered. Additionally, DON induced mitochondrial membrane potential decrease but ATP levels increase. DON can induce DNA damage, which in turn regulates apoptosis by regulating mitochondrial permeability by regulating p53 and in turn the Bcl-2 protein family. Furthermore, DON can activate the ATM-chk2-cdc25C and ATM-p53 signaling pathways to induce G2-phase cycle arrest in GES-1 cells. Finally, DON is able to enter the nucleus by simple diffusion, but does not directly target mitochondria. In conclusion, DON is able to enter the nucleus and cause DNA damage, apoptosis and cycle arrest in GES-1 cells. These results provide evidence for DON induced cytotoxicity and gastric disease.